2004
DOI: 10.1097/01.wnr.0000134846.79002.5c
|View full text |Cite
|
Sign up to set email alerts
|

Rapid neural differentiation of human cord blood-derived mesenchymal stem cells

Abstract: Human umbilical cord blood (UCB) contains hematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs), both of which are regarded as valuable sources for cell transplantation and cell therapy. Adherent cells expressing MSCs-related antigens such as SH2, CD13, CD29, and ASMA, have been isolated from a mononuclear cell fraction of human UCB. Under proneurogenic conditions, these UCB-derived adherent cells rapidly assumed the morphology of multipolar neurons. Both immunofluorescence and RT-PCR analyses indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 11 publications
0
49
0
1
Order By: Relevance
“…Six full-term UCB units, each containing about 80 mm of blood, were processed as previously described [24][25][26]. For the isolation of MSCs, MNCs were plated at a density of 1 × 10 6 cells per cm 2 and allowed to adhere to culture flasks for 5 days.…”
Section: Cell Growth and Total Rna Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Six full-term UCB units, each containing about 80 mm of blood, were processed as previously described [24][25][26]. For the isolation of MSCs, MNCs were plated at a density of 1 × 10 6 cells per cm 2 and allowed to adhere to culture flasks for 5 days.…”
Section: Cell Growth and Total Rna Isolationmentioning
confidence: 99%
“…UCB-derived cells were proven to be more advantageous in cell procurement, storage, and transplantation than their bone marrow (BM) counterpart and therefore better suited in tissue engineering and development of cell-based therapeutics. A number of reports from different laboratories [19][20][21][22][23], including ours [24][25][26], indicate that UCB-derived MSCs are highly similar to the cells of BM origin with respect to cell characteristics and multilineage differentiation potential. Therefore, this study may lead us to reveal the molecular signature that is specific to human MSCs but independent of their origins, and it will assist further studies on molecular mechanisms controlling various core stem cell properties.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that the umbilical cord blood contains cells that may express neuronal markers (Buzanska, Machaj, Zablocka, Pojda, & DomanskaJanik, 2002; Sanchez-Ramos et al, 2001). The umbilical cord is also a rich source of hematopoietic and mesenchymal stem cells (Wang et al, 2004) and has compelling potential for therapeutic use in neurological diseases due to the ability of these cells to differentiate into neural lineages (Buzanska et al, 2002;Jeong et al, 2004;Li et al, 2004;McGuckin, Forraz, Allouard, & Pettengell, 2004;Rogers & Casper, 2004;Sanchez-Ramos et al, 2001).…”
Section: Umbilical Cord Bloodmentioning
confidence: 99%
“…Therefore, HUCB is of significant value as good source of MSCs. Indeed, it was reported that HUCB-derived MSC (HMSCs) have multilineage differentiation activity rather than BM-derived MSC (20). Recently, numerous studies have ascribed not only potent tissue regeneration and repair but also anti-inflamatory effects of HMSCs in various diseases such as kidney disease, lung injury, hypoxia-induced brain injury, and liver cirrhosis (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%